Marriage and family - Demmitt, Kevin (Wadsworth, 2003)
This software-based workbook is an exciting way to get students to view marriage and family from the sociological perspective. With this workbook and accompanying ExplorIt software and data sets, your students will use national and cross-national survey to examine and actively learn marriage and family topics. This inexpensive workbook will add an exciting dimension to your marriage and family course